Cross-Border Relations During the Pandemic - Anna GARDZINSKA (Communications of International Proceedings, 2021)
International relations play a crucial role in the modern socio-economic geography and spatial planning, and regional development increasingly depends on cross-border interactions. The relations are the cornerstone of cross-border cooperation, one of the objectives of which is to integrate separate border areas into a single cross-border area. The Polish-German borderland is an example of a cross-border area development of which is determined mainly by effective relations based on cooperation. Cross-border cooperation plays reflects the quality of life, supports the movement of goods, people and capital, and it is important to overcome structural problems which are directly linked to the peripheral location of the area. The development and tightening of relations has been impeded by the spread of the COVID-19 pandemic which broke out in Europe in 2020. With the temporary closing of borders and border crossing restrictions (quarantine, negative Covid-19 test result), the development of cross-border relations had to change in terms of their quality and quantity. The purpose of the article is to underline the significance of cooperation in the Polish-German cross-border area, as well as to identify barriers to more intensive cooperation due to the spread of the COVID-19 pandemic.
Keywords: relations; cross-border cooperation; cross-border area; Polish-German border; COVID-19 pandemic